PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KETERLIBATAN KARYAWAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) YANG BERDAMPAK TERHADAP KINERJA PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPAT - Eka Rafida; Adrian Radiansyah (LPPM STIE PERTIBA Pangkalpinang, 2017)
This study aims to determine the influence of transformational leadership, organizational culture, work environment, and employee involvement, to Organizational Citizenship Behavior (OCB) Impact on the performance of public services in the Department of Population and Civil Registration of Central Bangka Regency. This research uses the quantitative approach with survey research method. The number of samples and population of 47 people from. The research instrument consists of a transformational leadership questionnaire, organizational culture, work environment, and employee engagement to the Organization Citizenship Behavior (OCB) that impact on performance.The results showed that: 1). the influence of Transformational Leadership, Organizational Culture, Work Environment, and Employee Engagement, simultaneously to Organizational Citizenship Behavior (OCB); 2) the influence of Transformational Leadership on Organizational Citizenship Behavior (OCB), 3). the influence of Organizational Culture on Organizational Citizenship Behavior (OCB), 4). the influence of the Work Environment on Organizational Citizenship Behavior (OCB), 5). influence of Employee Engagement on Organizational Citizenship Behavior (OCB), 6). the influence of Organizational Citizenship Behavior (OCB) on Performance.